The Microbiota-Gut-Brain Axis in Neuropsychiatric Disorders: Pathophysiological Mechanisms and Novel Treatments - Kim, Yong-Ku; Shin, Cheolmin (Current Neuropharmacology, 2018)
Background: The human gut microbiome comprise a huge number of microorganisms with co-evolutionary associations with humans. It has been repeatedly revealed that bidirectional communication exists between the brain and the gut and involves neural, hormonal, and immunological pathways. Evidences from neuroscience researches over the past few years suggest that microbiota is essential for the development and maturation of brain systems that are associated to stress responses. Method: This review provides that the summarization of the communication among microbiota, gut and brain and the results of preclinical and clinical studies on gut microbiota used in treatments for neuropsychiatric disorders. Result: Recent studies have reported that diverse forms of neuropsychiatric disorders (such as autism, depression, anxiety, and schizophrenia) are associated with or modulated by variations in the microbiome, by microbial substrates, and by exogenous prebiotics, antibiotics, and probiotics. Conclusion: The microbiota–gut–brain axis might provide novel targets for prevention and treatment of neuropsychiatric disorders. However, further studies are required to substantiate the clinical use of probiotics, prebiotics and FMT.
Keywords: Microbiota-gut-brain axis